ANALISIS KADAR FLAVONOID TOTAL PADA EKSTRAK DAUN SIRSAK (ANNONA MURICATA L.) DENGAN METODE SPEKTROFOTOMETRI UV-VIS. - Mukhriani Mukhriani; Faridha Yenny Nonci; Siti Munawarah (Jurnal Farmasi UIN Alauddin Makassar, 2015)
A research on the determination of the total flavonoid content of 70% ethanol extract and n-hexane extract of leaves of soursop(Annona muricata L.). The purpose of this study was to determine levels of total flavonoids, contained in soursop leaf extract (Annona muricata L). Extraction of chemical constituents from leaves of soursop(Annonamuricata L.) done by maceration method using 70% ethanol. To determine the flavonoid compounds in the sample extracts, compound analysis is carried out using UV-Vis spectrophotometer. The results were obtained levels of total flavonoids of the soursop leaf (Annona muricata L). Of 70% ethanol extract was 2,82%. And n-hexane extract was 4,48 %. So the total flavonoid content of the extract of soursop leaf (Annona muricata L.) by 7.3% .